Role of Samvardhana Ghrit in the Management of Childhood Disability Disorders: A Review - Marasingha, M N S; Ojha, Nisha Kumari Ojha (International Research Journal of Ayurveda & Yoga, 2022)
Today development disabilities are emerging as a new problem of society. While disability is discussed particularly in children, about a quarter of chronic childhood problems are neurological in origin. Disability treatment and management in the world is a big challenge. The Ayurveda medicine (like Vatashamaka drug and Medhya drug) and along with Panchkarma procedures will help at possible level for the rehabilitation towards lives with potential of independence. Samvardhana Ghrit is mentioned in the Lehadhyaya chapter of the Kashyapa Samhita. It is used to promote healthy growth of child without interference from disease, as well as to improve or treat impaired conditions in children who are Pangu (lame), Muka (dumb), Ashruti (deaf), and Jada (idiot). Aim: To evaluate the efficacy of Samvardhana ghrit in the management of childhood disability disorders. Materials and Methods: A literature review was conducted with the help of many important Ayurvedic and Modern textbooks, and article published in various journals. Result and discussion: Present review reveals that the ingredients of Samvardhana Ghrit have action on the brain and nervous system. Further, as the formulation is in ghrit form, it can easily cross the blood brain barrier and show its effect. Conclusion: Samvardhana Ghrit can be used for the management of childhood disability disorder. However, additional panchakarma and physiotherapy may provide additional benefit to the patients.